Peculiarities of using modeling methods of traffic flows in the city street network - Stepanchuk, Oleksandr; Lapenko, Oleksandr; Чернишова, Оксана Сергіївна (Theory and practice of design, 2022)
This study examines methods of modeling traffic flows within the city street network, identifies problems with their application and implementation in modern conditions of development and functioning of cities and livelihoods; summarizes approaches to existing models of traffic flow within the city street network. An analysis of the problems which are solved by applying the traffic flow theory can improve the conditions of movement of vehicles on highways within cities. The study identifies and analyses these problems and the methods for solving them. Functional classification of mathematical models of transport flows is substantiated, taking into account the traffic forecasting models for transport network, models of traffic flow dynamics, and models of optimization of transport network functioning. The article discusses and concludes the directions for improving the traffic flow management systems in the general city street network, as well as scientific concepts and theoretical provisions for the distribution of vehicles in the street network, in an attempt to solve real-time problems of optimal traffic flow management. By analyzing the existing methods of modeling traffic flows in the city street network, this study was able to develop a general concept of their implementation in an urban street traffic management system. The obtained scientific result serves as a basis for further theoretical and applied research on development of intelligent traffic control systems.